URBANISATION AND CULTURAL CONVERSION OF THE LOIS IN MANIPURI SOCIETY - Seram, Nirupama; Singh, Atom Sunil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This demography study deals with spatial development and cultural change from the rural state of isolation towards integrating urbanisation by Lois people of Manipur, India. Their movement carries challenges as well as losses for cultural continuity with opportunities to be stretched culturally. As an ancient penal practice confined them to rural locales, the Lois people bear with special resilience as well as transformative capacity within their socio-cultural substrates. This research explores how urban migration has changed their traditional lifestyle and cultural identity, responding to a very important question of the case of traditional communities as the Lois negotiating and maintaining their cultural essence in the midst of relentless pressures from modernisation and urbanisation. The main aspects looked into are: how urban migration transforms the traditional socio-cultural framework of the Lois and strategies they use to maintain the cultural identity in an urban setting. This study investigates broader implications of urbanisation for indigenous cultures through comprehensive analyses of migration patterns, cultural adaptation, and dual dynamics of preservation and change.